"Comparing the incomparable": Hospital costing and the art of medicine in post-war Britain. Issue 2 (June 2016) - Gebreiter, Florian
Abstract: This paper examines the relationship between medical and hospital accounting discourses during the two decades after the 1946 National Health Service (NHS) Act for England and Wales. It argues that the departmental costing system introduced into the NHS in 1957 was concerned with the administrative aspects of hospital costliness as contemporary hospital accountants suggested that the perceived incomparability, immeasurability and uncontrollability of medical practice precluded the application of cost accounting to the clinical functions of hospitals. The paper links these suggestions to medical discourses which portrayed the practice of medicine as an intuitive and experience-based art and argues that post-war conceptions of clinical medicine represented this domain in a manner that was neither susceptible to the calculations of cost accountants nor to calculating and normalising intervention more generally. The paper concludes by suggesting that a closer engagement with medical discourses may enhance our understanding of historical as well as present day attempts to make medicine calculable.